The effect of anteversion on femoral component stability assessed by radiostereometric analysis. - Gill, H; Alfaro-Adrián, J; Alfaro-Adrián, C; McLardy-Smith, P; Murray, D (2002)
Internal rotation of a femoral stem within the femur, with posterior migration of the femoral head (PHM) relative to the femur, is an important mode of failure. The relationship between anteversion and rotational stability for the Exeter (Howmedica International Ltd, London, UK) and Charnley Elite (DePuy International Ltd, Leeds, UK) stems was investigated using radiostereometric analysis (RSA). For the Elite, there was a significant (P=.01) correlation between anteversion and PHM, whereas for the Exeter, there was no significant correlation (P=.6). Increasing anteversion of the Elite was associated with decreasing PHM and increased stability. Of stems, 20% of the Elite and none of the Exeter were classified as having reduced rotational stability because their PHM was >2 SDs from the mean. All reduced rotational stability implants had anteversion substantially <20 degrees. Polished collarless tapered stems such as the Exeter seem to have enhanced rotational stability. For conventional stems, increasing anteversion increases stability. It is recommended that these stems are anteverted 20 degrees.